INTRAHEPATIC CHOLESTASIS OF PREGNANT WOMEN AFTER THE USE OF ASSISTED REPRODUCTIVE TECHNOLOGIES (World Science, 2021)
80 pregnant women were examined after assisted reproductive technology (ART) programs: 40 women with manifestations of intrahepatic cholestasis of pregnant women (IHP) - the main group and 40 women without manifestations of IHP (comparison group).In the majority (62.5%) of patients after ART, the diagnosis of IHP established after 30 weeks of pregnancy. Some patients (27.5%) reported short-term episodes of IHP up to 24 weeks of gestation. In 17.5% of women, IHP had a severe course. Almost a third (27.5%) of women are over 35 years old. Women with IHP have a significantly higher frequency of allergies in the anamnesis (35.0%), liver pathology (20.0%) and diseases of the gastrointestinal tract (25.0%). In one third of women, IHP developed repeatedly, 42.5% of the main patients indicated a family history burdened with IHP. Almost a third of women (27.5% vs. 12.5%, p